Estudi comparatiu i edició de l'Stabat mater d'Escorigüela. - SANCHIS MOLLÀ, HÈCTOR (Scripta, 2020)
Joan Baptista Escorigüela is the most interesting author of catalan poetry in Valencia at the end of the 18th century. Two of his best works are: El Àngel del Apocalispi and a version of the Stabat Mater Dolorosa. In this paper, we will carry out a comparative study between his version of Stabat Mater Dolorosa with the original. We will know the modifications made by the autor and we will get results that will allow us to set this poem in the pre-romantic style. Finally, we will end with an edition of it.